MicroRNA miR‐223 as regulator of innate immunity. Issue 3 (3rd July 2018) - Yuan, Xiaoyi; Berg, Nathaniel; Lee, Jae Woong; Le, Thanh‐Thuy; Neudecker, Viola; Jing, Na; Eltzschig, Holger
Abstract: MicroRNAs were discovered more than 2 decades ago and have profound impact on diverse biological processes. Specific microRNAs have important roles in modulating the innate immune response and their dysregulation has been demonstrated to contribute to inflammatory diseases. MiR‐223 in particular, is very highly expressed and tightly regulated in hematopoietic cells. It functions as key modulator for the differentiation and activation of myeloid cells. The central role of miR‐223 in myeloid cells, especially neutrophil and macrophage differentiation and activation has been studied extensively. MiR‐223 contributes to myeloid differentiation by enhancing granulopoiesis while inhibiting macrophage differentiation. Uncontrolled myeloid activation has detrimental consequences in inflammatory disease. MiR‐223 serves as a negative feedback mechanism controlling excessive innate immune responses in the maintenance of myeloid cell homeostasis. This review summarizes several topics covering the function of miR‐223 in myeloid differentiation, neutrophil and macrophage functions, as well as in inflammatory diseases including acute respiratory distress syndrome and inflammatory bowel disease. In addition, nonmyeloid functions of miR‐223 are also discussed in this review. Therapeutic enhancement of miR‐223 to dampen inflammatory targets is also highlighted as potential treatment to control excessive innate immune responses during mucosal inflammation. Abstract : MiR‐223 is important in regulating innate immune responses and recent studies highlight the therapeutic potential of enhancing miR‐223 as a treatment for inflammatory diseases.